AN ANALYSIS OF LANGUAGE FEATURES USED BY MEN AND WOMEN OF ENGLISH LANGUAGE EDUCATION (ELE) STUDENTS THROUGH WHATSAPP GROUP - Cahyani, Putu Anggun; Suwastini, Ni Komang Arie; Saputra, Nyoman Pasek Hadi; Padmadewi, Ni Nyoman (Lingua Scientia, 2025)
Men and women both use language as a crucial device for communicating with a variety of persons both inside and outside of their immediate area. Language use and communication depend on many factors, such as region, age, socioeconomic class, gender, and others. One of factors that can create language variation namely, gender. Language features refer to one of the linguistic variances brought on by social factors like gender. This study aims to compare how male and female English Language Education students use language in communication media such as WhatsApp, the function of the language features also. The design of this study was the descriptive qualitative method. The researcher used one instruments there is observation sheet. To analysed the data, researcherrecognizing and categorizing the 10 categories of Lakoff's linguistic properties (1975). The findings revealed that English LanguageEducation students in WhatsApp Group used only five types of language features, which were categorized as men’s and women’s language characteristics. These include intensifiers, rising intonation, tag inquiries, lexical hedges, and polite forms. Each of features have unique function in communication and the purpose for which it is used.